Organizational Climate and Work Environment with Prevention from Infection - Teorida Laia; Bustami Syam; Dewi Elizadiani Suza; Diah Arruum (Universitas Aisyah Pringsewu, 2022)
Prevention of infection is an action taken to reduce the incidence of infection in hospitals. Management of infection is assessed based on organizational climate and the nurse's work environment that shapes nurse behavior in preventing infection in the hospital. The study aimed to analyze the relationship between organizational climate and nurses' work environment in the prevention of infection in hospital Universitas Sumatera Utara. The study was a descriptive correlative. Data were collected using a questionnaire and analyzed using multiple linear regression. The sample was 135 nurses. The results show that the factor most associated with the prevention of infection is work environment (p=0,01; OR=2,76; 95%CI= 1,22-6,27) and organizational climate (p=0,02; OR=2,65; 95%CI=1,13-6,21). The work environment had the most dominant relationship with the prevention of infection in Hospital Universitas Sumatera Utara. It is expected that in the future hospital to improve the organizational climate by increasing the awarding and appreciation of nurses' work and creating a better and more conducive work environment, especially in the psychological environment of nurses, so that nurses remain motivated to work especially in preventing infections in hospitals. Abstrak: Pencegahan infeksi adalah tindakan yang dilakukan untuk mengurangi kejadian infeksi di rumah sakit. Penata laksanaan infeksi dinilai berdasarkan iklim organisasi dan lingkungan kerja perawat yang membentuk perilaku perawat dalam pencegahan infeksi di rumah sakit. Penelitian ini bertujuan untuk menganalisis hubungan iklim organisasi dan lingkungan kerja perawat dengan pencegahan infeksi di Rumah Sakit Universitas Sumatera Utara. Penelitian ini merupakan penelitian deskriptif korelatif. Data dikumpulkan dengan menggunakan kuesioner dan dianalisis menggunakan regresi linier berganda. Sampel penelitian adalah 135 perawat. Hasil penelitian menunjukkan bahwa faktor yang paling berhubungan dengan pencegahan infeksi adalah lingkungan kerja (p=0,01; OR=2,76; 95%CI= 1,22-6,27) daniklimorganisasi (p=0,02). ; OR=2,65; 95%CI=1,13-6,21). Lingkungan kerja memiliki hubungan paling dominan dengan pencegahan infeksi di Rumah Sakit Universitas Sumatera Utara. Diharapkan kedepannya rumah sakit dapat meningkatkan iklim organisasi dengan meningkatkan penghargaan dan apresias iterhadap kerja perawat serta menciptakan lingkungan kerja yang lebih baik dan kondusif khususnya di lingkungan psikologi perawat, sehingga perawat tetap termotivasi untuk bekerja khususnya dalam pencegahan infeksi di RS. Rumah sakit.